(Neuro)scienze e processo penale. Tra epistemologia scientifica ed epistemologia giudiziaria (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The relationship between (neuro)sciences and criminal trial is very articulated. (Neuro)Science, in fact, discuss around imputability, ability to rationally participate in a court process, and even free will. The use of scientific knowledge in the court requires careful study of the criminal justice system and particularly of the judicial epistemology and of the rights of the parties. It must be based on a proper analysis of the way we think about science too, because the way of looking at the science has implication on legal instruments and on their use.
Keywords: Scientific epistemology; judicial epistemology; scientific evidence; adversarial system; rights of parties